2017
DOI: 10.19030/jabr.v34i1.10097
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect The Nonpayment Of Municipal Services In Madibeng, Mamelodi And Soshanguve Townships Of South Africa

Abstract: The study was conducted in Madibeng, Mamelodi and Soshanguve townships of South Africa in order to assess and evaluate the main reasons for the non-payment of municipal services by members of the community. The study was conducted based on a stratified random sample of size 428 households. Statistical data analyses were performed by using methods such as ordered logistic regression analysis and Bayesian analyses. The results showed that 22% of households in Madibeng, 54% of households in Mamelodi and 78% of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…These SMMEs exist at various growth stages and are exposed to several challenges that affect their growth and success. For example, studies have identified bureaucracies, associated with business registration, as challenges that discourage business formalisation and affect overall SMME growth in the CoT [20][21][22]. Common regulatory challenges, highlighted in all these noted studies, include limited regulatory knowledge amongst SMMEs due to skills challenges; low information transfer; and costs-, time-, and process-related issues [20][21][22].…”
Section: Smmes In the City Of Tshwanementioning
confidence: 99%
See 4 more Smart Citations
“…These SMMEs exist at various growth stages and are exposed to several challenges that affect their growth and success. For example, studies have identified bureaucracies, associated with business registration, as challenges that discourage business formalisation and affect overall SMME growth in the CoT [20][21][22]. Common regulatory challenges, highlighted in all these noted studies, include limited regulatory knowledge amongst SMMEs due to skills challenges; low information transfer; and costs-, time-, and process-related issues [20][21][22].…”
Section: Smmes In the City Of Tshwanementioning
confidence: 99%
“…For example, studies have identified bureaucracies, associated with business registration, as challenges that discourage business formalisation and affect overall SMME growth in the CoT [20][21][22]. Common regulatory challenges, highlighted in all these noted studies, include limited regulatory knowledge amongst SMMEs due to skills challenges; low information transfer; and costs-, time-, and process-related issues [20][21][22]. Various CoT-based studies have also shown that corruption -especially pertaining to procurement-related irregularities -excludes many potential SMME suppliers from local government supply systems [20][21][22][23].…”
Section: Smmes In the City Of Tshwanementioning
confidence: 99%
See 3 more Smart Citations